PENYIDIKAN TINDAK PIDANA PENGANIAYAAN YANG DILAKUKAN OLEH SATUAN POLISI PAMONG PRAJA TERHADAP DEMONSTRAN DIKAITKAN DENGAN PERDAMAIAN YANG DILAKUKAN PARA PIHAK DI KEPOLISIAN RESOR KOTA PEKANBARU - Rodiah Mardhotillah; Mexsasai Indra; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Investigation of the efforts made by investigators seeking information and gather evidence that he explained crime. As for the criminal acts that often occur in the community that violence or persecution, the presence of such actions certainly abuse victims take legal steps by making a police report. In the passage of the investigation process is often the case for peace between the victim and reported. In this case the investigation of criminal offenses related to maltreatment by Civil Service Police Unit against demonstrators associated with the peace made by the parties in the resort city of Pekanbaru police. The purpose of this thesis, namely: First, the Crime Investigation persecution conducted by Civil Service Police Unit Against Protesters, Second, Crime Persecution Peace Process conducted by Civil Service Police Unit Against Protesters Can Be The Reason For Termination of Investigation Process.This type of research can be classified in this type of sociological juridical research because in this study the authors directly conduct research on the locations or places studied in order to provide a complete and clear picture of the issues examined. This research was conducted at the City Police Pekanbaru, while the sample population is a whole party with regard to the issues examined in this study, the data source diginakan, primary data, secondary data and tertiary data collection techniques in research in the observation , interviews and a literature review.From the research, there are two fundamental rights problem that can be inferred. First, Investigation Crime of Torture conducted by Civil Service Police Unit Against Protesters, that the criminal acts of persecution carried out by the Civil Service Police Unit has memenuhui element of the sentence, but in terms of the passage of the investigation, Warrant Commencement of Investigation (SPDP) was never delivered to the public prosecutor (prosecutor). As Article 109 of the Criminal Procedure Code since the start of the investigation the investigator must give written notification of the commencement of the investigation. Second, the Peace Process Crime persecution conducted by Civil Service Police Unit Against Protesters Can Be The Reason For Termination Process of Investigation, while the peace process made by the victim and reported, in line with the Letter of the Chief of Police No. Pol: B / 3022 / XII / 2009 / SDEOPS, dated December 14, 2009 on Alternative Dispute Case Handling Through Resolusion (ADR). Selanjtnya for legal certainty investigation process carried his case to terminate the investigation. Suggestions Authors are expected to police in conducting the investigation in order to convey Warrant Commencement of Investigation to the Public Prosecutor, Second, should the parties in particular reported that the contents of the peace mematuhui not repeat such actions dkemudian day.Keywords: Investigation - Persecution - Peace